Implementasi User Centered Design dan Software Requirements Specification pada Perancangan Website - Kurniawan, Dedy; Passarella, Rossi; Fardinelly, Syahria; Anggraini, Febrina Hedy; Mattjik, Hani Alifia; Rahmayuni, Septa (Institut Teknologi Garut, 2024)
Significant changes in learning approaches, methods and tools in the digitalization era have given rise to the need for Student E-Worksheets (E-LKPD) which can advance students' critical and creative thinking abilities. This research designs E-LKPD based on government regulations using the User Centered Design (UCD), Software Requirements Specification (SRS) and System Usability Scale (SUS) methods. Through the UCD design stages, E-LKPD succeeded in creating a user-friendly website that complies with the learning rules for students in secondary schools. This research aims to produce digital-based teaching materials in the form of E-LKPD by implementing User Centered Design (UCD) and Software Requirements Specification (SRS). The results were proven through Usability Testing using the System Usability Scale (SUS) approach, obtaining a score of 80.667 with the grade A category, Excellent in Adjective, Acceptable, and the Promoter category in the Net Promoter Score (NPS) which shows that E-LKPD has been successfully designed with good usability and suitable for use according to user needs.